2013
DOI: 10.1681/asn.2012020154
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Tubule Proliferation Is Insufficient to Induce Rapid Cyst Formation after Cilia Disruption

Abstract: Disrupting the function of cilia in mouse kidneys results in rapid or slow progression of cystic disease depending on whether the animals are juveniles or adults, respectively. Renal injury can also markedly accelerate the renal cyst formation that occurs after disruption of cilia in adult mice. Rates of cell proliferation are markedly higher in juvenile than adult kidneys and increase after renal injury, suggesting that cell proliferation may enhance the development of cysts. Here, we induced cilia loss in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
7
39
0
1
Order By: Relevance
“…[13][14][15]20 It is likely that a combination of several processes (i.e., cell death, proliferation, epithelial dedifferentiation, altered planar cell polarity, and inflammation) underlie the injury-induced acceleration of cystogenesis. 14,34 Although several types of renal injuries in mice with scattered Pkd1 deletion led to increased likelihood of cyst formation ( Figure 3B), these injuries never triggered a rapid disease onset, and most of the renal parenchyma remained normal. The lack of a rapid disease onset after renal injury in our scattered Pkd1 deletion model, therefore, differs from previous data.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15]20 It is likely that a combination of several processes (i.e., cell death, proliferation, epithelial dedifferentiation, altered planar cell polarity, and inflammation) underlie the injury-induced acceleration of cystogenesis. 14,34 Although several types of renal injuries in mice with scattered Pkd1 deletion led to increased likelihood of cyst formation ( Figure 3B), these injuries never triggered a rapid disease onset, and most of the renal parenchyma remained normal. The lack of a rapid disease onset after renal injury in our scattered Pkd1 deletion model, therefore, differs from previous data.…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies of the role of cilia in cystic syndromes suggest a bifurcated action dependent on the context of the initiating lesion (36)(37)(38)(39). Although loss of cilia due to inactivating mutations in IFT proteins can independently induce cystogenesis, recent strong evidence supports the idea that in the context of lesions in Pkd1 that cause defective signaling from cilia, the removal of cilia suppresses cyst formation (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Although loss of cilia due to inactivating mutations in IFT proteins can independently induce cystogenesis, recent strong evidence supports the idea that in the context of lesions in Pkd1 that cause defective signaling from cilia, the removal of cilia suppresses cyst formation (36,37). Our data are consistent with these results; moreover, although activation of Src, ERK, and mTOR pathway signaling was not found to be necessary for cystogenesis linked to mutation of Pkd1 (36,37), our work also showed that loss of Nedd9 in the context of a Pkd1 mutation activated these pathways. Although Nedd9 is typically a positive regulator of these proteins, studies of forced oncogene-dependent proliferation of cells in a Nedd9 −/− genotype indicate that loss of Nedd9 can cause reflexive hyperactivation of ERK and other proliferative signaling proteins (15).…”
Section: Discussionmentioning
confidence: 99%
“…Chez l'adulte, ces nouvelles voies de formation de kystes contrôlées par le cil seraient supprimées en présence des polycystines fonctionnelles. De même, d'autres travaux, se fondant sur des modèles de lésion du rein chez l'adulte, suggèrent que les altérations de la prolifération ne peuvent pas être seules en cause dans la genèse des kystes chez les souris mutantes pour Ift88 ou Kif3a, dont le cil est altéré, et un rôle important des processus d'acquisition de la polarité cellulaire a été en effet proposé [26,41].…”
Section: Fonction Du Cil Dans Les Tubules Rénauxunclassified